Roles of P2X4 and P2X7 purinergic receptors in inflammatory responses of macrophages and microglia - Faria, Beatriz de Andrade de (2024)
The purinergic P2X4 and P2X7 purinergic receptors are expressed in a myriad of cells in the innate immune system. Their activity is elicited when ATP molecules are bound to their structure, allowing the formation of ion channels permeable to cations such as K+, that leaves the intracellular medium, and Ca2+ and Na+ that enter the intercellular space. The change in homeostatic ionic concentrations leads to downstream signaling pathways that determine cell fate. This study focuses on the role of P2X4 and P2X7 purinergic receptors in the innate immune system and its participation in pyroptosis. Pyroptosis is a lytic and proinflammatory form of cell death that allows the leakage of pro-inflammatory molecules like ATP and cytokines. Once in the extracellular medium, the scenario is amplified through the inducement of a pro-inflammatory phenotype in the neighbouring cells, triggering signaling pathways that are detrimental to cell viability. Therefore, it is proposed that activated P2X7 and P2X4 receptors are proposed to have a role in pyroptotic cell death and propagation of pro-inflammatory signaling. The signaling pathway of the NLRP3 inflammasome is relevant in this study, as it is a fundamental component of the signaling pathway that allows cell death by pyroptosis. The NLRP3 inflammasome is activated by the efflux of K+ ions through ion channels formed by the addressed purinergic receptors. The subsequent cleavage of proteins by the inflammasome leads to the formation of pro-inflammatory cytokines and pores thatresult in the loss of integrity of the plasma membrane and, consequently, the leakage of intracellular content. The focus of this work is human microglia and bone marrow derived macrophages, key players of the innate immune system. In the first place, it tackles a human microglial novel cell line, the C20 line, as a possible model for studies in microglial inflammation. The investigation of this cell lines suitability to the present investigation was deemed necessary due to the current limited number of studies using this novel model. Secondly, bone marrow derived macrophages, a well-established model for inflammatory responses, was used to further investigate the participation of purinergic P2X4 and P2X7 receptors in lytic cell death. C20 cells were stimulated by LPS, and pro-inflammatory responses were evaluated. Among these responses, upregulation of inflammation-relevant gene, viability, ROS production, nitrate production was determined. After this gamut of investigations, C20 cells were evaluated as unfit for the continuation of the studies in pro-inflammatory cell death due to lack of response to the stimuli with LPS. However, the purinergic P2X4 receptor was upregulated in this cell line after LPS exposure, being the only result that deviated from the overall inert behaviour. In bone marrow derived macrophages, the establishment of its inflammatory response was determined unnecessary due to the wide use of these cells in studies that tackle pro-inflammatory responses. Pharmacological modulation of P2X4 and P2X7 purinergic receptors, concomitant to the inducement of lytic cell death, was carried on after the confirmation of their expression in the model and the upregulation of P2X4 receptors upon LPS stimuli. Through lytic cell death and membrane integrity assays, the modulation of the P2X7 purinergic receptor with antagonists has proven to be an efficientway to prevent lytic cell death. However, the use of P2X4 receptor antagonists has shown no influence. These observations put the purinergic P2X7 receptor as the only one responsible for lytic cell death. However, the upregulation of the purinergic P2X4 receptor in both bone marrow derived macrophages and C20 cells should be recognized as an indication of its participation in the establishment of the pro-inflammatory phenotype through molecular pathways that remain unclear.